The Impact of Foreign Direct Investment (PMA), Domestic Investment (PMDN), and Remittances on Per Capita Income in Indonesia - Eka Agustiani; Vina Aprianti (Westscience Press, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI), Domestic Investment (DI), and remittances on per capita income in Indonesia. The study uses panel data from 34 provinces in Indonesia during the 2013–2023 period obtained from Statistics Indonesia (BPS), Bank Indonesia, and the Ministry of Investment/BKPM. The analytical method used is panel data regression with the assistance of EViews 10 software. Model selection was conducted through the Chow test, Hausman test, and Lagrange Multiplier (LM) test, resulting in the Common Effect Model (CEM) as the best model. The results indicate that partially, FDI, DI, and remittances do not have a significant effect on per capita income in Indonesia. Simultaneously, FDI, DI, and remittances also do not significantly affect per capita income. The adjusted R-square value of 0.44% indicates that variations in per capita income are largely influenced by other variables outside the research model. Therefore, the increase in per capita income in Indonesia is not only influenced by investment and remittances, but also by other factors such as human resource quality, infrastructure, and government expenditure.